Utilization practices and conservation impacts of endangered wildlife in asian countries - Abdullah-Fauzi, Nurfatiha Akmal Fawwazah; Othman, Nursyuhada; Haris, Hidayah; Nur Hartini Sariyati, Nur Hartini Sariyati; Ramli, Farah Farhana; Sufahani, Suliadi Firdaus; Md Zain, Badrul Munir; Mohd-Ridwan, Abd Rahman; Aifat, Nor Rahman; Mohamed, Mohd Sanusi; Ibnu Maryanto, Ibnu Maryanto; Abdul-Latiff, Muhammad Abu Bakar (2023)
The Asian region is globally renowned for its unparalleled biodiversity, rich ecosystems, and unique cultural heritage. However, the delicate equilibrium between human societies and the diverse flora and fauna faces increasing challenges due to the region's rich biodiversity and escalating utilization of wildlife resources. Hence, this paper aims to document the utilization of endangered wildlife across Asian countries and to report the existing conservation measures and recommendations for sustainable wildlife management over the years. We employed prominent academic databases, specifically SCOPUS, to explore the dynamics of wildlife utilization and its associated implications. From the findings, 9,989 records were successfully identified. However, only 65 articles were included in the review after the screening process. A total of 61 species, comprising 30 mammals, 22 reptiles, one amphibian, and eight birds, all endangered, were identified as subjects of wildlife utilization in 16 Asian countries. China possessed the highest count for wildlife utilization across all categories, including 15 species used for trading purposes. In conclusion, this research underscores the critical need for integrated approaches that balance human needs and conservation imperatives to ensure a sustainable future for Asia's wildlife biodiversity